Geospatial approach to determine Soil bearing capacity of Nagpur city, Maharashtra India. Issue 1 (June 2021) - Khan, Farhan; Das, Bhumika
Abstract: Geological Information System (GIS) is a technique which can make geotechnical investigation easy for engineering purpose. It helps the engineer to analyze the ground data before physical inspection of the site. The area of research is the Nagpur district of Maharashtra, India. The topographic sheet for Nagpur is 55K/16 and 55O/4 of 2010. The Major purpose of this research was to determine the bearing capacity map, Contour map, and total land cover/land use map for a different purpose. From the above map, it will be easier for engineers to decide the type of Foundation and the trend of development across the city. Earlier, there was no method to store bore log and soil data to the exact location of the borehole, but today with the help of the Geospatial technique, researchers can assign soil data with every borehole. Nowadays, urbanization is speedily taking place due to which proper utilization is necessary for land according to its strength and properties. In this research, the author wants to collect different satellite imageries of Nagpur city and bore logs comprising of geotechnical data. The predicted outcome should show the contour map, elevation map, changes in land use pattern, and bearing capacity across the city. These help the researcher and engineers who are working in the same area for future site selection.